2018
DOI: 10.1021/acschemneuro.8b00239
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Localization of Galanin in Zebrafish Telencephalon and Anticonvulsant Effect of Galanin Overexpression

Abstract: Galanin is a neuropeptide widely expressed in the nervous system, but it is also present in non-neuronal locations. In the brain, galanin may function as an inhibitory neurotransmitter. Several studies have shown that galanin is involved in seizure regulation and can modulate epileptic activity in the brain. The overall goal of the study was to establish zebrafish as a model to study the antiepileptic effect of galanin. The goal of this study was achieved by (1) determining neuroanatomical localization of gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 83 publications
(179 reference statements)
1
14
0
Order By: Relevance
“…For example, the two galanin-expressing cell types in our dataset may potentially influence dozens of cell types throughout the telencephalon, consistent with the widespread distribution of galanin-immunoreactive fibers. 69 Generally, broadcasting networks are consistent with global functions of neuromodulation such as the control of brain states.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the two galanin-expressing cell types in our dataset may potentially influence dozens of cell types throughout the telencephalon, consistent with the widespread distribution of galanin-immunoreactive fibers. 69 Generally, broadcasting networks are consistent with global functions of neuromodulation such as the control of brain states.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate if galanin by itself is able to reduce whole-brain activity, we employed a transgenic approach by using hsp70l:gal 10 expressing larvae. These transgenic fish express galanin under the control of the heatshock promoter hsp70l , enabling the induction of galanin expression by upregulating transcripts by over 300 fold 11 . Attempts to induce galanin overexpression through heat shock were discontinued due to a notable impact on the brain activity of wild type larvae compared to non-exposed wild type larvae (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1). Yet, considering that hsp70l:gal larvae already display a basal elevation of galanin transcripts by approximately 8-fold 11 , comparable with the upregulation seen in eaat2a -/- mutants and PTZ rebound (Figure 1C and 1F), we chose to use larvae without inducing transcription via heat shock. We performed Ca 2+ imaging and found that indeed elevated expression of galanin in hsp70l:gal larvae leads to a decrease in whole-brain activity (Figure 2A) compared to wild type siblings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, changes in galn expression after PTZ administration were not observed, which is consistent with previous reports. [49] Galanin is also expressed in many tissues outside the nervous system, so it might be concluded that changes in brain expression are masked by expression in other organs, as was postulated for c-fos. It should also be mentioned that it is not clear whether galanin expression is increased during the seizures, with some studies finding no changes in galanin levels in particular brain regions [50].…”
Section: Discussionmentioning
confidence: 99%